(untitled) (Jurnal Teknologi (Sciences & Engineering), 2025)
Despite the growing interest of industrial practitioners and users in applying exoskeleton technology to augment physical strength, the usability aspect of the assistive device is still a great challenge to product designers and engineers. This paper aims to review the critical factors that affect the usability of passive lower-limb exoskeletons to improve user acceptance on the device technology. Additionally, this paper discusses the current trends, challenges, and future research directions to improve the usability aspects of the exoskeletons. The authors collected journal articles related to exoskeleton technology published from 2016 to 2023. The articles were accessed from digital databases, Scopus and Web of Science. A total of 54 articles written in English were selected for final review. Based on the literature, the authors identified seven critical factors: effectiveness, efficiency, engagement, error tolerance, ease of learning, portability, and stability, all of which have a substantial influence on the usability of a passive lower-limb exoskeleton. A mapping of associations between the seven critical factors and the System Usability Scale reveals good agreement in terms of usability assessment criteria. Product designers and engineers will undoubtedly find the new knowledge gained from this review helpful when conducting usability studies on the passive lower-limb exoskeletons.